Increased Adverse Pregnancy Outcomes Associated With Stage 1 Hypertension in a Low-Risk Cohort: Evidence From 47 874 Cases. Issue 3 (March 2020) - Wu, Dan-dan; Gao, Ling; Huang, Ou; Ullah, Kamran; Guo, Meng-xi; Liu, Ye; Zhang, Jian; Chen, Lei; Fan, Jian-xia; Sheng, Jian-zhong; Lin, Xian-hua; Huang, He-feng
Abstract : The recommendations for the diagnosis of stage 1 hypertension were recently revised by the American Heart Association primarily based on its impact on cardiovascular disease risks. Whether the newly diagnosed stage 1 hypertension impacts pregnancy complications remain poorly defined. We designed a retrospective cohort study to investigate the associations of stage 1 hypertension detected in early gestation (<20 weeks) with risks of adverse pregnancy outcomes stratified by prepregnancy body mass index. A total of 47 874 women with singleton live births and blood pressure (BP) <140/90 mm Hg were included, with 5781 identified as stage 1a (systolic BP, 130–134 mm Hg; diastolic BP, 80–84 mm Hg; or both) and 3267 as stage 1b hypertension (systolic BP, 135–139 mm Hg; diastolic BP, 85–90 mm Hg; or both). Slightly higher, yet significant, rates and risks of gestational diabetes mellitus, preterm delivery, and low birth weight (<2500 g) were observed in both groups compared with normotensive controls. Importantly, women with stage 1a and stage 1b hypertension had significantly increased incidences of hypertensive disorders in pregnancy compared with normotensive women (adjusted odds ratio, 2.34 [95% CI, 2.16–2.53]; 3.05 [2.78–3.34], respectively). After stratifying by body mass index, stage 1a and 1b hypertension were associated with increased hypertensive disorders in pregnancy risks in both normal weight (body mass index, 18.5–24.9; adjusted odds ratio, 2.44 [2.23–2.67]; 3.26 [2.93–3.63]) and the overweight/obese (body mass index, ≥25; adjusted odds ratio, 1.90 [1.56–2.31]; 2.36 [1.92–2.90]). Current findings suggested significantly increased adverse pregnancy outcomes associated with stage 1 hypertension based on the revised American Heart Association guidelines, especially in women with prepregnancy normal weight. Abstract : Supplemental Digital Content is available in the text.